2017
DOI: 10.1038/cddis.2017.119
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106b and miR-93 regulate cell progression by suppression of PTEN via PI3K/Akt pathway in breast cancer

Abstract: Accumulating evidences have revealed that dysregulated microRNAs (miRNAs) involve in the tumorigenesis, progression and even lead to poor prognosis of various carcinomas, including breast cancer. MiRNA-106b-5p (miR-106b) and miRNA-93-5p (miR-93) levels were confirmed to be significantly upregulated in breast cancer clinical samples (n=36) and metastatic cell line (MDA-MB-231) compared with those in the paired adjacent tissues and normal breast epithelial cell line (MCF-10A). Moreover, further research stated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 38 publications
3
113
2
Order By: Relevance
“…We only identified miR‐145‐5p as being associated with BRCA1, IGF1, PDGFRA, THBS1, CHRM2 , and TNXB . Other miRNAs associated previously with genes in PI3K/Akt‐signaling pathway include miR‐590‐5p, 106b, and miR‐93 with PTEN , miR‐497 with IGF1R, miR‐451 with LKB1, AKT, PI3K , and BCL2 , and miR‐126 with AKT . We observed associations between miR‐497 and miR‐106b‐5p with various genes in the pathway.…”
Section: Discussionsupporting
confidence: 62%
“…We only identified miR‐145‐5p as being associated with BRCA1, IGF1, PDGFRA, THBS1, CHRM2 , and TNXB . Other miRNAs associated previously with genes in PI3K/Akt‐signaling pathway include miR‐590‐5p, 106b, and miR‐93 with PTEN , miR‐497 with IGF1R, miR‐451 with LKB1, AKT, PI3K , and BCL2 , and miR‐126 with AKT . We observed associations between miR‐497 and miR‐106b‐5p with various genes in the pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, of the 13 miRNAs included in our signature, there is limited evidence regarding the role of hsa-miR-125-5p in breast cancer progression, while there is some evidence to suggest that miR-301-5p stimulates proliferation and invasion (26) and that hsa-miR-196-5p and hsa-miR-340-5p inhibit progression (27,28). For hsa-miR-30-5p, hsa-miR-130-5p, hsa-miR-93-5p, hsa-miR-503-5p, and hsa-miR-205-5p, there is conflicting evidence regarding their roles in breast cancer progression, with some reports suggesting functions that operate to increase the risk of progression and others suggesting the reverse (29)(30)(31)(32)(33)(34)(35). The apparently conflicting evidence regarding the roles of specific miRNAs in breast cancer prognosis is consistent with the observation that some miRNAs exert both oncogenic and tumor suppressive effects (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that KLF4 was regulated by miR-103 in breast cancer 19 ; however, the function of miR-103 and KLF4 in lung cancer still F I G U R E 3 miR-103 is a target of TRHDE-AS1. A, miR-103-binding sequences in the 3′-UTR of TRHDE-AS1 and mutant sites in 3′-UTR of TRHDE-AS1.…”
Section: Klf4 Is a Target Of Mir-103mentioning
confidence: 99%